On the Image Pixels Classification Methods - Ghimire, Santosh (Journal of the Institute of Engineering, 2019)
In this article, we first discuss about the images and image pixels classifications. Then we briefly discuss the importance of classification of images and finally focus on various methods of classification which can be implemented to classify image pixels.